Optimalisasi Ibadah Intergenerasional sebagai Upaya Penguatan Komunitas Jemaat GKSI Sui Deras Estate dalam Meningkatkan Kesejahteraan - Marten Bainkabel (Lembaga Pengembangan Kinerja Dosen, 2025)
Involvement across generations in church worship remains a significant challenge in building a solid and inclusive congregation community. At GKSI Sui Deras Estate, worship tends to be divided according to age groups, which limits spiritual interaction between generations. This creates a gap between younger and older congregation members, ultimately affecting the harmony and cohesion of the community. This community service program aims to optimize intergenerational worship as an effort to strengthen social and spiritual cohesion among the congregation by fostering mutual respect and enhancing relationships between generations. The activities began with an initial observation to identify the issues and needs of the congregation concerning worship. Based on the observation findings, a worship design was created involving representatives from various age groups, ensuring that each generation could feel included in the worship experience. This design process also took into account aspects that could bridge generational differences, such as the selection of hymns, liturgical readings, and approaches that were appropriate for different age groups. In addition, intergenerational liturgy training was conducted to ensure that worship could proceed harmoniously, with active participation from all age groups, from children to the elderly. Intergenerational worship was conducted periodically, providing opportunities for the entire congregation to interact and experience unity in worship. The results of these activities showed a significant increase in participation from congregation members of various ages. A sense of mutual respect between generations grew, something that had previously been lacking. This intergenerational worship also contributed to the strengthening of the community's identity as one body in Christ, where every member, regardless of age, felt valued and involved. Overall, intergenerational worship has proven to be a relevant and practical approach to strengthening the congregation community in a sustainable way, creating a more inclusive and loving atmosphere among fellow congregation members.